Endothelial adhesion molecules in acute ischemic stroke: A cross-sectional evaluation of VCAM-1 and ICAM-1 as potential biomarkers of severity - Nur, Haris; Amran, Muhammad Yunus; Akbar, Muhammad; Ladju, Rusdina Bte; Tammasse, Jumraini; Juliana, Anastasi (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Stroke is a leading cause of death and disability worldwide, with ischemic stroke being the most common type. Neuroinflammation plays a pivotal role in ischemic brain injury, where endothelial adhesion molecules such as vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1) mediate leukocyte recruitment and blood–brain barrier disruption. This study aimed to investigate the association between circulating VCAM-1 and ICAM-1 levels and stroke severity in patients with acute ischemic stroke. Methods: An analytical observational study with a cross-sectional design was conducted at Dr. Wahidin Sudirohusodo Central General Hospital and affiliated facilities in Makassar, Indonesia, from June to August 2025. Fifty-eight first-ever acute ischemic stroke patients aged 18–70 years were consecutively recruited. Stroke severity was assessed using the National Institutes of Health Stroke Scale (NIHSS) within 1–7 days of onset. Venous blood samples were collected and analyzed for VCAM-1 and ICAM-1 levels. Statistical analyses included Spearman correlation and comparative tests, with p < 0.05 considered significant. Results: The mean age of patients was 58.2 years, with a male predominance (53.4%). Hypertension (58.6%) was the most common risk factor. Most patients presented with minor (44.8%) or moderate (48.3%) severity. Mean VCAM-1 and ICAM-1 levels were 38.62 ng/mL and 18.16 ng/mL, respectively. No significant correlation was observed between VCAM-1 (r = 0.098, p = 0.462) or ICAM-1 (r = –0.050, p = 0.708) and NIHSS scores. However, a significant association was found between VCAM-1 levels and stroke severity in non-hypertensive patients (r = 0.420, p = 0.041). Conclusions: Circulating VCAM-1 and ICAM-1 levels were not significantly associated with overall stroke severity in acute ischemic stroke. VCAM-1 may have prognostic relevance in specific subgroups, but larger longitudinal studies are warranted to clarify their biomarker potential.